Improving irrigation water use efficiency of robusta coffee (Coffea canephora) production in Lam Dong Province, Vietnam - Tran, D.N.L.; Nguyen, T.D.; Pham Thu Thuy; Rañola, R.F.; Nguyen, T.A. (MDPI, 2021)
Recent prolonged dry periods and lack of irrigation water have severely affected the productivity of coffee farms in the Central Highlands of Vietnam. This paper analyzes the efficiency of irrigation water use for Robusta coffee (Coffea canephora) in the Lam Dong province. A Cobb–Douglas production function was used to determine coffee productivity’s response to the application of irrigation water and other production factors using data collected from 194 farmers, while the technical efficiency (TE) and irrigation water use efficiency (IWUE) were analyzed using a data envelopment analysis (DEA) model. The correlation of different factors to IWUE was determined using the Tobit model. The production function analysis using Cobb–Douglas shows that the volume of irrigation water, amount of working capital, labor, and farm size significantly influence coffee productivity. Indigenous farmers are more efficient in utilizing irrigation water than migrant farmers. The Tobit result indicates that farmers’ experience, education level, the distance of farm to water sources, security of access to water sources, extension contact, and credit access significantly affect IWUE. The study findings further suggest that mitigating water shortages in coffee farms require subregional and national policy support such as better access to credit and extension services, training, land management, and household-level efforts to improve farming practices through the application of appropriate technologies and traditional knowledge.